2017
DOI: 10.1093/ejo/cjx015
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of piezosurgery technique in miniscrew supported en-masse retraction: a single-centre, randomized controlled trial

Abstract: This work was supported by Başkent University Research Fund. No conflict of interest was declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
88
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(105 citation statements)
references
References 25 publications
10
88
2
4
Order By: Relevance
“…The results demonstrated that group I showed a statistically significant decrease in time needed for extraction space closure than group II for the upper and lower arches. This observation was in agreement with other studies (16,17) which reported reduced RAP effect when a flap was not reflected.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results demonstrated that group I showed a statistically significant decrease in time needed for extraction space closure than group II for the upper and lower arches. This observation was in agreement with other studies (16,17) which reported reduced RAP effect when a flap was not reflected.…”
Section: Discussionsupporting
confidence: 93%
“…For group II (flapless technique), the results of the current study for retraction time was consistent with Tuncer et al, (17) for the upper arch. For the lower arch, no data was found in the available literature concerning the evaluation of piezocision for en-masse retraction of the lower anterior segment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the studies that reported retraction rates, ours falls within the range (0.51-0.85 mm/month) mentioned for miniscrew-supported en masse retraction without any intervention for rapid tooth movement. 7,57 When the numbers are taken into consideration, it is fair to say that retraction rate did not show a substantial increase. This can be explained with the fact that the anterior unit in this patient was composed of 7 teeth, unlike conventional en masse retraction.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some of the cases treated with piezoincision-assisted orthodontics are canine distalization, en masse retraction, incisor decrowding, compensation of Class II and Class III malocclusions, and expansion. [3][4][5][6][7][8] Invasive cervical resorption (ICR) is a type of external root resorption that starts beneath the epithelial attachment and progresses toward the pulp chamber, which then changes direction apically and coronally once it reaches the predentin. 9 It circumvents the pulpal tissue and spreads in all 3 dimensions in a nontraditional way.…”
mentioning
confidence: 99%